Farmakogenomika v zdravljenju astme - Berce, Vojko (Farmacevtski vestnik, 2008)
There are substantial differences in the effect of antiasthmatic therapy between individuals which are dependent on the diversity of the genetic code. The purpose of pharmacogenomics is to find out those polymorphisms, which are connected with all effects of certain drug. For now the pharmacogenomics of asthma above all study the influence of the genes which code for drug receptors, signal transduction components and transcription factors. Most studies were done in the field of pharmacogenomics of beta2 agonists. Gene mutations that are known to alter the response to asthma therapy include Arg/Arg at position 16 in ADRB2 gene, mutations of LTC4S and ALOX5 and CRHR1 variants. The goal of pharmacogenomics is to find out most efficient drug without adverse side effects individually suited for each patient on basis of his genotype.
Keywords: asthma; astma; farmakogenomika; polimorfizmi